CHARACTER EDUCATION OF A LEADER IN THE DANCE THEATRE “THE MERCY OF DURGA DEVI” - Yulianti, Dewi; Ni Nyoman Kasih; I Ketut Sumerjana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Moral degradation such as corruption, murder, divorce, and others which are currently faced by Indonesia is the reason for the significance of character education in Indonesia. Apart from character education, it can also be carried out through performing arts in the form of dance theatre. Dance theatre which always contains moral values ​​is very beneficial for the audience which can be measured from character values. This study aims to find out the metaphors used in the dialogue and the values ​​of the national character contained in the dance theatre The Mercy of Durga Devi and the moral values ​​contained in the dance theatre. The method used is descriptive qualitative method, which includes three stages, namely (1) data collection stage, (2) data analysis stage, and (3) the presentation of results analysis stage. The results of the study show that the dance theatre The Mercy of Durga Devi, which was adapted from Srimad Bhagavatam, contains metaphors that make conveying character values ​​easier and more interesting to understand. The values ​​of the national character are religious, creative, tolerant, responsible, peace-loving, and independent which convey the message which every leader must carry out the scriptures, do yadnya, and give charity.